(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 1999)
The publication posits that the short stories and chronicles of Manuel Puig have not dampened the literary world’s interest in the novels of the writer, which continue to provoke readings and re-readings by critics. It is precisely about reading in Geneviève Fabry’s book, Character and Reading in Five Novels by Manuel Puig. The author’s working hypothesis is that “the character is constructed in reading” (p. 23). The methodological support for her analysis comes from reception theories developed by the Constanza school and some works (mostly French) that were done in this perspective during the last decade.